Spatial Relations in the Indonesian Locative Preposition of â€œDi Atasâ€: a Study of Cognitive Semantics - Joko Kusmanto; Sarmedi Agus Siregar; Mariahari Mariahati (BAHASTRA, 2021)
This study examines the spatial relation of the preposition "di atas" (above, over, on) in Indonesian using cognitive semantic theory. This study aims to discover (i) the conceptual structure of the preposition â€œdi atasâ€ spatial relation and (ii) its extended use in the conceptual mapping. This study used descriptive qualitative method. The cognitive data were collected from three groups of subjects, each consisting of ten people. These three groups of subjects are also used as the source triangulation to elicit the conceptual structure of the preposition "di atas" (above, over, on). Meanwhile, the data on the prepositionâ€™s extended use in the conceptual mapping were collected from online media. The results suggest that the conceptual structure of the preposition "di atas" (above, over, on) has two kinds of image schemas, namely (i) the VERTICALITY image schema which is based on its orientation and (ii) the ANTARA image schema and the TOPANGAN image schema which are based on its topology. The two kinds of image schemas are general in nature and are specified as definitive lingual units based on the speaker's different perceptions of the position of the related entities. Another important research finding is that prepositions that have been seen as closed words can be used metaphorically through conceptual mapping. This shows that prepositions have an important role in structuring human mind. The results of the study also found and reinforced the construal nature of meaning conceptualization.